How do people feel about sleep diaries? Factors influencing sleep diaries completion with and without daily exposure to light - Boris Gass; Grégory Pierné; Elisabeth Ruppert; Ulker Kilic-Huck; Laurence Hugueny; Patrice Bourgin; Juliette Chambe (PLoS ONE, 2025)
Study Objectives Sleep diary is a common tool in sleep medicine, but was barely validated in practice so far. Lack of light exposure is associated with sleep disorders, especially insomnia. For that purpose, our team developed a sleep diary with information about light exposure. Our objectives were to compare the proportion of informative usual sleep diaries (USD) and light/sleep diaries (LSD) and to evaluate factors influencing the quality of filling them. Methods A monocentric, prospective, controlled interventional study was conducted. Patients included were randomized into two parallel groups: distribution of an USD (used in common practice), versus distribution of a LSD (similar to the USD but with light exposure data). The main outcome was the proportion of diaries returned and correctly filled out. A multivariate logistic regression model was then used to identify factors associated with the correct filling. Results A total of 325 USD and 324 LSD were distributed. 295 (45.5%) diaries were returned by patients: 158 (48.6%) USD, 137 (42.3%) LSD. The proportion of correctly completed diaries was 25.2% for USD versus 20.4% for LSD, which corresponds to a difference in the proportion of −4.86% [−10.25%; +∞[. The hypothesis of non-inferiority of LSD compared to USD cannot therefore be retained for a non-inferiority threshold of −10%. Multivariate analysis identified the level of difficulty experienced by the patient as an important factor influencing the quality of completion (OR =  0.99 [0.979–0.998]). The proportion of returned sleep diaries was greater in the USD and LSD insomniac subgroup (p < 0.0001). Conclusions The non-inferiority of this new diary was not reached but this study highlighted the importance of clear explanations, patient motivation and restricted amount of collected data. Interestingly, insomniac patients represent a major target population for this tool.